Hak Memperoleh Pekerjaan bagi Penyandang Disabilitas Fisik di Kota Bandung di Masa Pandemi Covid-19 - Didan Akbar Zaelani; Ade Yunita Mafruhat (UNISBA Press, 2022)
Abstract. It appears that the biggest obstacle for people with disabilities during the Covid-19 pandemic is the difficulty of mobility. to find out to what extent Covid-19 has impacted persons with physical disabilities in obtaining the right to work. During the Covid-19 era, people with physical disabilities in the city of Bandung faced any obstacles, what were the inhibiting factors and supporting factors for people with physical disabilities to get a job. The research method used a qualitative approach with a descriptive method. This research was conducted using a purposive sampling technique for informants, involving 22 persons with disabilities from 12 sub-districts with physical disabilities in the city of Bandung. The method of analysis in this research is qualitative, interactive and continuous to completion. Data analysis uses data reduction, visualization, and conclusion drawing techniques, as well as triangulation techniques to assess the effectiveness of the data. Access to job information and training is still not good, people with physical disabilities have difficulty finding work during the Covid-19 pandemic, Current educational background become an assessment for job providers to select workers, companies are looking for workers who have quality and without physical deficiencies, stigma arises because they think that people with physical disabilities will find it difficult to face the world of work. The right to work for people with disabilities is still far from ideal and expectations . It can be seen from the four factors that hinder the lack of information about job opportunities for people with disabilities and job training, discrimination that is still carried out by some employers in the recruitment process, difficulties in finding work during the Covid-19 period and the minimal level of education of people with physical disabilities. This supporting factor is the existence of a law regulation. Abstrak. Muncul bahwa hambatan terbesar bagi penyandang disabilitas di masa pandemi Covid-19 adalah sulitnya bermobilitas. untuk mengetahui sejauh mana Covid-19 berdampak kepada penyandang disabilitas fisik dalam memperoleh hak atas pekerjaan. apakah dimasa Covid-19 penyandang disabilitas fisik di Kota Bandung menghadapi hambatan apa saja faktor penghambat yang dihadapi dan faktor pendukung bagi penyandang disabilitas fisik untuk memperoleh pekerjaan Metode penelitian menggunakan pendekatan kualitatif dengan metode deskriptif. Penelitian ini dilakukann menggunakan Teknik purposive sampling untuk pengambilan informan, dengan melibatkan 22 penyandang disabilitas dari 12 kecamatan disabilitas fisik di Kota Bandung. Metode analisis dalam penelitian ini adalah kualitatif, interaktif dan berkesinambungan hingga tuntas. Analisis data menggunakan teknik reduksi data, visualisasi, dan penarikan kesimpulan, serta teknik triangulasi untuk menilai keefektifan data.akses terhadap informasi lapangan kerja dan pelatihan masih belum baik, penyandang disabilitas fisik mengalami kesulitan mencari pekerjaan dimasa pandemi Covid-19, Latar belakang pendidikan saat ini menjadi penilaian bagi penyedia lapangan kerja untuk menyeleksi tenaga kerja, perushaaan mencari tenaga kerja yang memiliki kualitas dan tanpa kekurangan fisik, stigma muncul karena beranggapan para penyandang disabilitas fisik akan sulit untuk menghadapi dunia kerja.Hak atas pekerjaan bagi penyandang disabilitas masih jauh dari ideal dan harapan. dapat dilihat dari empat faktor penghambat kurangnya informasi tentang kesempatan kerja bagi penyandang disabilitas dan pelatihan kerja, diskriminasi yang masih dilakukan oleh sebagian pengusaha dalam proses perekrutan, kesulitan mencari kerja di masa Covid-19 dan minimnya tingkat pendidikan para penyandang disabilitas fisik. faktor pendukung ini dengan adanya peraturan Undang-Undang.